2011
DOI: 10.1177/153567601101600305
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Microorganisms on HEPA Filters

Abstract: High Efficiency Particulate Air (HEPA) filters are required to minimize the release of microorganisms from laboratories and other settings. This study was carried out to assess whether a range of microorganisms captured on HEPA filters would survive under normal operating conditions. Bacillus atrophaeus (NCTC 10073), Staphylococcus epidermidis (NCIMB 12721), MS-2 coliphage, Escherichia coli (NCIMB 9481), Brevundimonas diminuta (NCIMB 11091), and Aspergillus brasiliensis (ATCC 16404) were individually aerosoliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The HEPA filters have a significantly greater life-span compared with respirator masks even with the potential re-sterilization of masks (12,13). This is a pilot study of the potential modification of SS with HEPA filters and would require further testing to confirm a recommended life-span for operating, establishing timing of regular quality assurance checks on the efficacy of the filters, and possible further modification of the inlet to protect the HEPA filter material (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The HEPA filters have a significantly greater life-span compared with respirator masks even with the potential re-sterilization of masks (12,13). This is a pilot study of the potential modification of SS with HEPA filters and would require further testing to confirm a recommended life-span for operating, establishing timing of regular quality assurance checks on the efficacy of the filters, and possible further modification of the inlet to protect the HEPA filter material (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…47 Regarding biological matter, it is well documented that mechanical filtration may present a risk of contamination and proliferation because the surface of fibrous filters, where microorganisms and nutrients accumulate, can represent a suitable ecosystem for microorganisms growth. 35,48 For ESP, research has shown that electrical charging could impair the survival rates of bacterial cells and spores, thus limiting their proliferation. 49,50 Consequently, over the last decade, ESPs have gained increasing attention for the removal of particulate matter (mainly dust particles and airborne microorganisms) in confined indoor spaces.…”
Section: F I G U R E 1 Simplified Flow Chart Of a Typical Air Supply ...mentioning
confidence: 99%
“…The shortages of supply and high demand may have increased the price significantly, causing consumers to tend to use them for an extended period of time. However, besides the discomfort feeling and the difficulty in adapting the wearing of face masks for a long time, the SARS-CoV-2 virus may oculate and remain viable on the outer side of the respirator for approximately 3−5 days, but can be as long as 14 days [1] , [2] , thereby the extended use of respirators may increase the risk of infection besides causing unexpected health problems, as air-borne bacteria may also be intercepted by respirators’ filter media [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“…When using face masks, the host's saliva and sweat may nurture and create an ideal environment for these bacteria and viruses to remain viable on the surface [3] . This survivability is of utmost concern because in addition to new pathogens, such as SARS-CoV-2, having the potential to coexist with a broad range of bacteria [4] , the accumulation of air-borne bacteria, especially the commensal pathogen Staphylococcus aureus ( S. aureus ), may pose unexpected threats to the wearers’ health.…”
Section: Introductionmentioning
confidence: 99%